TOLERANSI DALAM QS. AL-MUMTAHANAH AYAT 8: BELAJAR BERBUAT BAIK KEPADA YANG BERBEDA - Hidayatulloh, Jihan Kharisma; Kautsar, Nur 'Alim Muhammad; Nurrahman, Muhammad Kiflain; Abdulmatin, Ammar; Nurrohim, Ahmad (LPPM STAI Muhammadiyah Probolinggo, 2026)
The increasing prevalence of intolerance, hate speech, and socio-religious polarization in Indonesia highlights the urgent need to reaffirm Qur'anic ethical values in social relations. This study examines QS. Al-Mumtahanah [60]:8 as a normative foundation for tolerance grounded in al-birr (active social goodness) and al-qisth (proportional justice), a verse that has received relatively limited focused attention in Qur'anic tolerance studies. Employing a qualitative approach with a thematic-contextual (maudhu'i-contextual) method, this research treats QS. Al-Mumtahanah:8 as the primary data, supported by classical and modern Qur'anic commentaries. The analysis integrates linguistic, historical (asbab al-nuzul), and comparative approaches to the interpretations of Muslim exegetes. The findings demonstrate that tolerance in this verse is not conceived as passive conflict avoidance, but as an active ethical commitment to benevolence and justice toward those of different faiths who do not engage in hostility. This study proposes a constructive and applicable model of Qur'anic tolerance relevant to Indonesia's multicultural society and contributes to the strengthening of religious moderation and inclusive Islamic literacy.